PERANAN PEMERINTAH DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA INDUSTRI BATU BATA (STUDI KASUS DESA TANJUNG MULIA KECAMATAN PAGAR MERBAU KABUPATEN DELI SERDANG) - Putri, Mutia Aisyah; Lubis, Khairunnisah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The development of the brick industry MSMEs continued to increase in Tanjung Mulia Village, Pagar Merbau Subdistrict, making the government's role very important for empowering brick industry MSMEs. The purpose of this research was to identify and describe the government's role in empowering brick industry MSMEs in Tanjung Mulia Village, Pagar Merbau Subdistrict, and to analyze the inhibiting factors in the empowerment of MSMEs in the brick industry. The theory used in this research was the theory of government roles by Yusuf Ilyas (2014), employing a qualitative methodology. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the government’s role in empowering brick industry MSMEs in Tanjung Mulia Village was effective, as evidenced by the government's role as a regulator, contributing to business licensing and capital. The government's role as a dynamizer was seen in its collaborative programs with partnerships, and its role as a facilitator provided marketing facilities through partnerships. The obstacles in empowering brick industry MSMEs were the lack of available capital, the brick production process that had not fully utilized technology, and the competitiveness of brick sales.